PENGARUH ENVIRONMENT CONTROL TERHADAP HUBUNGAN ANTARA PARTISIPASI ANGGARAN DENGAN KINERJA PEMERINTAH (Studi Empiris pada SKPD Di Kabupaten Aceh Besar) - Jalaluddin Jalaluddin; Khairul Ibad (Program Magister Akuntansi Unsyiah, 2010)
The performance of government, particularly local governments still have to be improved because it has a very important role in serving the community. Improving the performance of government can be improved with variable budget participation because it can increase the effectiveness of the subordinates’ performance. The budget participation will be more effective by applying the Control Environment variables which is the core of the internal control system of government.This research was conducted on existing SKPD Aceh Besar . This study aims to find out the influence of the Control Environment on the relationship between budget participation and the performance of government. The samples used were the heads of esselon on existing SKPD in Aceh Besar district as many as 88 people of 54 SKPD that obtained by stratified random sampling method. The data used is primary data obtained through the distributing of questionnaires to the officials in SKPD involved the arranging of budget participation which analyzed by using multiple linear regression models and then this test is coupled with t-test and f-test, to see the influence of Control Environment on the relationship between budget participation and the performance of government. The influence is individually or unity.Partially, the result of research showed that budget participation, Control Environment, and interaction between budget participation and Control Environment significantly influence to the performance of government. Simultaneously it indicates that budget participation and Control Environment significantly influence the performance of government. The best implementation of budget participation and Control Environment will further increase the performance of government. Keywords: the performance of government, budget participation, and Control Environment.